CSR Disclosures in the Mining Industry: Empirical Evidence from Listed Mining Firms in Indonesia - Rina Asmeri; Tika Alvionita; Ardi Gunardi (Universitas Pasundan, 2017)
Companies that are involved in CSR strive to meet the expectations of stakeholders. Therefore, CSR and CSR reporting are tools of legitimacy to demonstrate its obedience (legitimacy theory). This study aims to look at empirical evidence on the effect of profitability and environmental performance on CSR disclosure. This study examined the target population of mining companies listed on the Indonesian Stock Exchange that included the CSR reporting in the 2010-2014 annual report, obtained a sample of 18 companies. By using multiple regression analysis test, there is no significant influence between profitability to CSR disclosure, whilst environmental performance has effect on CSR disclosure.